Apparent overconsolidation of mudstones in the Kumano Basin of southwest Japan: Implications for fluid pressure and fluid flow within a forearc setting. (25th April 2013) - Guo, Junhua; Underwood, Michael B.; Likos, William J.; Saffer, Demian M.
Abstract: [1] The Kumano Basin is located in the Nankai Trough subduction zone of southwest Japan. During the past 1.6 million years, approximately 800 meters of sandy turbidites and hemipelagic mud were deposited near the distal edge of the forearc basin, at Site C0002 of the Integrated Ocean Drilling Program. Constant‐rate‐of‐strain consolidation tests yield estimates of in situ permeability that range from 2.6 × 10 −17  m 2 to 2.5 × 10 −18  m 2 ; overconsolidation ratios range from 1.7 to 2.6, and values of the compression index range from 0.39 to 0.78. Several processes contributed to the apparent overconsolidation. Strata dip toward land, and pore fluids probably migrate up‐dip and vent along a bathymetric notch near the seaward edge of the basin. Efficient lateral drainage through sandy turbidites has kept pore pressures within interbeds of mudstone at (or close to) hydrostatic. In addition, alteration of dispersed volcanic glass, precipitation of authigenic clay minerals, and collapse of random grain fabric has probably strengthened the bonding among grains. Cementation is particularly likely within the lower basin (unit III), where values of porosity remain anomalously high. If fluid overpressures (and underconsolidation) exist anywhere within the basin, the most likely loci are where sandy turbidites terminate against impermeable mudstones along landward‐dipping on‐lap surfaces. Those types of on‐lap geometries, in addition to structural closures, might provide promising targets for oil/gas accumulation in other forearc basins, particularly where petroleum source rocks have been buried to the optimal depths of catagenesis. Key Points: Values of preconsolidation pressure indicate overconsolidation. Drainage through landward‐dipping turbidites leads to hydrostatic pore pressure. Cementation in the lower basin is responsible for apparent overconsolidation.